Item and source memory for emotional associates is mediated by different retrieval processes. (August 2020) - Ventura-Bort, Carlos; Dolcos, Florin; Wendt, Julia; Wirkner, Janine; Hamm, Alfons O.; Weymar, Mathias
Abstract: Recent event-related potential (ERP) data showed that neutral objects encoded in emotional background pictures were better remembered than objects encoded in neutral contexts, when recognition memory was tested one week later. In the present study, we investigated whether this long-term memory advantage for items is also associated with correct memory for contextual source details. Furthermore, we were interested in the possibly dissociable contribution of familiarity and recollection processes (using a Remember/Know procedure). The results revealed that item memory performance was mainly driven by the subjective experience of familiarity, irrespective of whether the objects were previously encoded in emotional or neutral contexts. Correct source memory for the associated background picture, however, was driven by recollection and enhanced when the content was emotional. In ERPs, correctly recognized old objects evoked frontal ERP Old/New effects (300–500 ms), irrespective of context category. As in our previous study (Ventura-Bort et al., 2016b), retrieval for objects from emotional contexts was associated with larger parietal Old/New differences (600–800 ms), indicating stronger involvement of recollection. Thus, the results suggest a stronger contribution of recollection-based retrieval to item and contextual background source memory for neutral information associated with an emotional event. Highlights: Memory performance for neutral items encoded in emotional and neutral contexts is mainly driven by the subjective experience of familiarity. Memory performance for correct background sources is based on recollection processes, particularly for emotional ones. Correctly recognized old items evoke an overall early frontal (300–500 ms) ERP Old/New effect. Late parietal (600–800 ms) ERP Old/New effects are exclusively evoked by old items associated with emotional backgrounds. Emotion effects on item and (background) source memory are driven by recollection processes.